A Survey of Artificial Intelligence Techniques Applied in Energy Storage Materials R&D - Luo, Ziyi; Yang, Xinyi; Wang, Yingxue; Liu, Weidi; Liu, Siliang; Zhu, Yuankun; Huang, Zihan; Zhang, Hong; Dou, Shuming; Xu, Jie; Tian, Jiachen; Xu, Kui; et al. (Frontiers in Energy Research, 2020)
Energy shortage is a severe challenge nowadays. It has affected the development of new energy sources. Artificial intelligence (AI) , such as learning and analyzing, has been widely used for various advantages. It has been successfully applied to predict materials, especially energy storage materials. In this paper, we present a survey of the present status of AI in energy storage materials via capacitors and Li-ion batteries. We picture the comprehensive progress of AI in energy storage materials, including the advantages and disadvantages of material data to support AI. Finally, we provide some ideas to solve those challenges.